Growing Eucalypt Outside its Native Range: A Review on Suitability and Beneficial Role - Prajapati, Brajkishor; Sarvade, S.; Prajapati, Jaya; Shrivastava, Atul Kumar; Singh, Mrigendra (International Journal of Bio-resource and Stress Management, 2024)
Eucalypt is an industrial short rotation fast growing tree species (SRFGTs), having wide range regarding climatic and edaphic requirements in Indian subcontinent. Eucalyptus camaeldulensis, E. globulus, E. grandis, E. tereticornis and E. citriodora are the widely planted eucalyptus species for different purposes in the country. Oil extracted from E. globulus has medicinal value and used to inhibit the avian influenza virus H11N9, and has wide scope in cosmetics, perfume, food, beverages, phytotherapy and aromatherapy. Oil contain p-coumaric, gallic, gentisic, p-hydroxybenzoic, syringic and vanillic acids and catechol are the responsible for retarding seed germination growth and survival of Parthenium, Solanum lycopersicum, Lactuca sativa and Agrostis stolonifera. Burning of eucalypt leaves used as mosquito repellent and compound 1, 8 cineole of eucalypt oil damage and kills Pediculus humanus capitis and lice. Aqueous solutions extracted from different parts of eucalypt showed nematocidal properties. Maize, wheat, mustard, berseem, potato, lentil are agricultural crops widely grown under eucalypt based agroforestry systems. Wider spacing of eucalypt in block plantations or boundary plantation mostly adopted in the agroforestry systems. Eucalypt sequester carbon 6 – 43 Mg C ha-1 yr-1 under plantations and agroforestry systems. The species has potential to reclaim waterlogged sites and escalate soil health through improving soil physical, chemical and biological properties. In case of economic returns from eucalypt based agroforestry systems, it gives nearly 1.5 B:C ratio.